2010
DOI: 10.1007/978-3-642-15880-3_39
|View full text |Cite
|
Sign up to set email alerts
|

Expectation Propagation for Bayesian Multi-task Feature Selection

Abstract: Abstract. In this paper we propose a Bayesian model for multi-task feature selection. This model is based on a generalized spike and slab sparse prior distribution that enforces the selection of a common subset of features across several tasks. Since exact Bayesian inference in this model is intractable, approximate inference is performed through expectation propagation (EP). EP approximates the posterior distribution of the model using a parametric probability distribution. This posterior approximation is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…Also we propose two hierarchical sparse models using Spike and Slab priors and relate them to HiLasso and C-HiLasso. Prior works using Spike and Slab priors for multi-task learning problems [15,16] only consider the block sparsity among different tasks while our work consider both the block sparsity across tasks and the group sparsity inside each task.…”
Section: Relation To Prior Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Also we propose two hierarchical sparse models using Spike and Slab priors and relate them to HiLasso and C-HiLasso. Prior works using Spike and Slab priors for multi-task learning problems [15,16] only consider the block sparsity among different tasks while our work consider both the block sparsity across tasks and the group sparsity inside each task.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…Different techniques can be used such as sampling methods or approximation methods. We choose expectation propagation (EP) because of its efficiency and demonstrated success for multi-task learning problems [16].…”
Section: Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…Since γ and β are given, the VG algorithm reduces to iterate eqs. (8) and (9) starting from a random m. Similarly, the PMF reduces to perform an E-step given the fixed hyperparameter values.…”
Section: Boston-housing Dataset: Vg Vs Pmfmentioning
confidence: 99%
“…Traditional studies are based on a strict assumption that selected variables are shared among all tasks [22,27]. Recent studies have suggested a more flexible approach that involves selecting variables by decomposing a coefficient into a shared part and an individual part [12,15] or factorizing a coefficient using a variable specific part and a task-variable part [32]. Although the variable selection approach provides better interpretability than the other approaches, it has limited ability to share common information among related tasks.…”
Section: Introductionmentioning
confidence: 99%